Counseling and assistance in verification and validation of housing data for surveyors - Wahyu Sejati; Lili Kusumawati; Giraldi Fardiaz Kuswanda; Ryan Faza Prasetyo; Avelina Nathania Bennediktus Suhardjo Pusoko (Community Empowerment, 2024)
The data collection of housing database in Jembatan Besi Village conducted by surveyors from the Faculty of Civil Engineering and Planning, Trisakti University often encounters data errors and obstacles during its implementation. These errors can be in the form of incorrect writing of addresses, family card numbers, head of family NIKs, or geotagging (location points) of buildings. Therefore, in the middle of the data collection, a workshop was held to analyze and evaluate the data that had been entered and to correct data errors. The method used is through data checking by field coordinators and repairs are carried out simultaneously. Workshop activities include presentation of the progress of the 50% survey results, data validation and verification, and data correction. During the workshop, the survey results were obtained as much as 60.55% with a total of 2,704 buildings and data correction facilities including geotagging, RT and RW data, Family Card Numbers, NIK, address writing, and deleting duplicate data.